Plasma evolution and continuum lowering in hot dense matter generated by X-ray free electron lasers - Ciricosta, O (2014)
The advent of the 4th generation X-ray sources paves the way for a new phase of experimental investigation of Hot-Dense plasmas. At the Linac Coherent Light Source (LCLS), pulses of keV X-rays, shorter than 100 fs, and with intensities up to 1018 W·cm-2, are routinely produced, allowing for the production of uniform samples of solid-density plasmas. The simple single-photon X-ray absorption mechanism can be easily modelled, so that the plasma conditions can be accurately retrieved, without relying on diagnostic techniques that are not benchmarked in this high density regime. The work presented here describes the results of the first experiment where the LCLS interacts with a solid Al target, isochorically heating it at temperatures up to 190 eV. The system is described by the SCFLY non-LTE model, where the density and temperature are computed self consistently, as a consequence of the detailed atomic processes, rather than imposed by the user. The approximations affecting the simulations are discussed in detail. The code is first validated, by modelling the charge state distribution measured in a previous experiment (L. Young et. al), where the LCLS interacts with a Ne gas, a simplified (collisionless) problem. Then it is used to model the K-alpha spectroscopic data obtained for Al. The plasma evolution, explained by SCFLY simulations, is found to be primarily determined by collisions, whose visible effects on the experimental spectra are discussed. By varying the wavelength of the laser and observing the change in the K-alpha fluorescence, the K-edges for different ions in the plasma were determined, leading to a charge resolved measurement of continuum lowering in the HDM system. The results disagree with the widely used Stewart-Pyatt model, with the disagreement increasing for higher charge states, but are consistent with the older Ecker-Kroell model. These results have profound implications for dense plasma modelling.